Pengaruh Pelayanan Sistem Online, Tarif, dan Publikasi Terhadap Keputusan Pembelian Secara Online Tiket Kereta Api Relasi Semarang – Jakarta (Studi Kasus Pada PT.Kereta Api Indonesia DAOP IV Semarang Tawang) - Wasiun, Rosyid; Nugraha, Hari Susanta; Prabawani, Bulan (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
PT.KAI is a transportation company that provides online purchase. High public interest for purchasing online ticket, make PT.KAI presenting the latest innovations in order to facilitate the users of the railway. This study aimed to determine the effect of an online system services, tariffs, and the publication of the decision purchasing Â train tickets online relationships Semarang and Jakarta. The type of this research is eksplanatory research with data collection tool is questionnaire. This study uses the 100 respondents who made a purchase train tickets online relationships Semarang and Jakarta. The sampling technique of this study was accidental sampling. The analysis instrument is validity test and reliability test. Data analysis that used is correlation coefficient, coefficient of determination, simple linear regression, t test, multiple linear regression, and F test.Based on the results of analysis show that in partial service online system contributes influence on purchasing decisions online by 14.4%, variable rates contributed influence on purchasing decisions online by 10.1% and publications variables contributing influence on purchasing decisions online at 8.1%. Simultaneously service online systems, tariffs, and publications contributing influence on purchasing decisions online at 21.2%. The conclusion of this study shows online system services, tariffs, and publications partially and simultaneously influence purchasing decisions online train tickets relation Semarang and Jakarta. Based on these results, PT.Kereta Api Indonesia DAOP IV Semarang must be able to maintain and continue to develop online systems services, the tariffs that were set according to the expected benefits for the consumer, and PT.KAI expected to increase the intensity of publications and information dissemination channel diversity.